The PASTIS trial: Testing tadalafil for possible use in vascular cognitive impairment. Issue 12 (8th February 2022) - Pauls, Mathilde M.H.; Binnie, Lauren R.; Benjamin, Philip; Betteridge, Shai; Clarke, Brian; Dhillon, Mohani‐Preet K.; Ghatala, Rita; Hainsworth, Fearghal A.H.; Howe, Franklyn A.; Khan, Usman; Kruuse, Christina; Madigan, Jeremy B.; et al.
Abstract: Introduction: There are few randomized clinical trials in vascular cognitive impairment (VCI). This trial tested the hypothesis that the PDE5 inhibitor tadalafil, a widely used vasodilator, increases cerebral blood flow (CBF) in older people with symptomatic small vessel disease, the main cause of VCI. Methods: In a double‐blind, placebo‐controlled, cross‐over trial, participants received tadalafil (20 mg) and placebo on two visits ≥7 days apart (randomized to order of treatment). The primary endpoint, change in subcortical CBF, was measured by arterial spin labelling. Results: Tadalafil increased CBF non‐significantly in all subcortical areas (N = 55, age: 66.8 (8.6) years) with greatest treatment effect within white matter hyperintensities (+9.8%, P  = .0960). There were incidental treatment effects on systolic and diastolic blood pressure (–7.8, –4.9 mmHg; P  < .001). No serious adverse events were observed. Discussion: This trial did not identify a significant treatment effect of single‐administration tadalafil on subcortical CBF. To detect treatment effects may require different dosing regimens.